Penulisan Naskah Menggunakan Model AIDA dan Story Brand dalam Pembuatan Video Company Profile Educourse - Bella Nurokta Fitria Hidayat; Bayu Suriaatmaja Suwanda; Siska Mulyawaty (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This project aims to implement the AIDA and StoryBrand models in writing the script for the Educourse company profile video, with the aim of increasing the effectiveness of business communication. This project uses a practice-based approach by compiling a structured script through the integration of the AIDA (Attention, Interest, Desire, Action) model to create a persuasive message and the StoryBrand framework to strengthen narrative coherence. The writing process includes identifying core messages, compiling an outline, and creating a final draft based on the principles of strategic communication and storytelling. The result of this project is a final script ready for production, containing the latest information about the company, user testimonials, and visual directions optimized for the YouTube digital platform. The application of both models allows for clearer, more engaging messages that are in line with Educourse's mission and audience. This project emphasizes the importance of implementing a structured communication model in media production and can be a reference in writing scripts that focus on branding strategies in the future. In addition, this project also contributes to the development of academic discourse in the field of digital content writing through the application of relevant theoretical approaches.